2020
DOI: 10.1017/dmp.2020.485
|View full text |Cite
|
Sign up to set email alerts
|

Municipality-Level Predictors of COVID-19 Mortality in Mexico: A Cautionary Tale

Abstract: Objective Local characteristics of populations have been associated with COVID-19 outcomes. We analyze the Municipality-level factors associated with a high COVID-19 mortality rate of in Mexico. Methods We retrieved information from cumulative confirmed symptomatic cases and deaths of COVID-19 as of June 20th, 2020 and data from most recent census and surveys of Mexico. A negative binomial regression model was adjusted, dependent variable was the COVID-19 deaths and the independent varia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…18,20,23,[29][30][31] As for the spatial analysis, ten studies were selected, which investigated which risk factors were associated with deaths in the studied areas and in certain populations. 1,19,24,29,30,[33][34][35][36][37] In these investigations, different techniques were used, among them: empirical Bayesian estimate (EBE); 37 geographically-weighted random forest (GW-RF); 1 geographically-weighted regression (GWR); 33 spatial Durbin model; 30 Least Absolute Shrinkage and Selection Operator (LASSO); 24 space-time scanning techniques (discrete Poisson model); [34][35][36] spatial correlation (Moran's Index); 29,30,33,37 and Pearson's correlation. 29,34,37 With the use of such tools, a heterogeneous distribution of deaths and/or mortality rates was evidenced, with socioeconomic and environmental conditions 1,19,29,30,33 and population density 24,29,30,35,37 being explanatory factors for the occurrence of events in these territories in space and space-time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,20,23,[29][30][31] As for the spatial analysis, ten studies were selected, which investigated which risk factors were associated with deaths in the studied areas and in certain populations. 1,19,24,29,30,[33][34][35][36][37] In these investigations, different techniques were used, among them: empirical Bayesian estimate (EBE); 37 geographically-weighted random forest (GW-RF); 1 geographically-weighted regression (GWR); 33 spatial Durbin model; 30 Least Absolute Shrinkage and Selection Operator (LASSO); 24 space-time scanning techniques (discrete Poisson model); [34][35][36] spatial correlation (Moran's Index); 29,30,33,37 and Pearson's correlation. 29,34,37 With the use of such tools, a heterogeneous distribution of deaths and/or mortality rates was evidenced, with socioeconomic and environmental conditions 1,19,29,30,33 and population density 24,29,30,35,37 being explanatory factors for the occurrence of events in these territories in space and space-time.…”
Section: Resultsmentioning
confidence: 99%
“…47 Other studies have also shown other health conditions associated with deaths, such as neurological, 20,32 respiratory, kidney diseases 12,27,38 and obesity. 20,21,35 In addition to biological and clinical factors, other factors that influenced mortality due to COVID-19 were socioeconomic, environmental and spatial distribution of the disease in the area of residence. Research conducted in 209 countries around the world, 29 in which spatial analysis techniques were used, such as global and local Moran's Index, in addition to multivariate logistic regression, identified the association of economic factors and population density related to mortality from the disease, establishing that mortality rates were associated with low economic level and higher population density in low-and middle-income countries.…”
Section: Alshogranmentioning
confidence: 99%
See 1 more Smart Citation
“…Ríos et al found that patients lived in municipalities with the highest overcrowding had a higher risk of dying from COVID-19 as compared to those who lived in a municipality with low overcrowding [63]. Likewise, Contreras et al and Villa et al reported population density as a factor associated to higher mortality rates and adverse results for COVID-19, respectively [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…diversas políticas se han adoptado para contener su propagación, sin embargo, determinantes en salud como pobreza, desempleo, inseguridad laboral, condiciones laborales, soporte social, afectan la evolución de la enfermedad. Además, factores como pertenecer a población indígena, población económicamente activa, dedicarse a actividades económicas esenciales y densidad de población, se han asociado a altas tasas de mortalidad por COVID-19 así como la prevalencia de enfermedades crónicas (2).…”
unclassified